2020
DOI: 10.1038/s41467-020-16250-4
|View full text |Cite
|
Sign up to set email alerts
|

FMRP(1–297)-tat restores ion channel and synaptic function in a model of Fragile X syndrome

Abstract: Fragile X Syndrome results from a loss of Fragile X Mental Retardation Protein (FMRP). We now show that FMRP is a member of a Cav3-Kv4 ion channel complex that is known to regulate A-type potassium current in cerebellar granule cells to produce mossy fiber LTP. Mossy fiber LTP is absent in Fmr1 knockout (KO) mice but is restored by FMRP(1-297)-tat peptide. This peptide further rapidly permeates the blood-brain barrier to enter cells across the cerebellar-cortical axis that restores the balance of protein trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 56 publications
0
33
1
Order By: Relevance
“…Future studies must also continue to make use of spatial and temporally restricted deletion of FMR1 to parse the contribution of different cell-types, brain regions, and developmental timepoints to FXS phenotypes. The development of FMRP-tat peptides to reintroduce different FMRP segments to FMR1 KO neurons is a powerful tool for dissociating FMRPs function via direct protein-protein interactions from its canonical role in translational regulation (Zhan et al, 2020 ; Park et al, 2021 ). Finally, the development of novel FXS models—such as the FMR1 KO rat (Till et al, 2015 ; Golden et al, 2019 ; Auerbach et al, 2021 ) and FXS human derived iPS cells (Telias et al, 2013 ; Bhattacharyya and Zhao, 2016 ) and organoids (Kang et al, 2021 ), will help identify which phenotypes are most highly conserved across species and highlight new treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies must also continue to make use of spatial and temporally restricted deletion of FMR1 to parse the contribution of different cell-types, brain regions, and developmental timepoints to FXS phenotypes. The development of FMRP-tat peptides to reintroduce different FMRP segments to FMR1 KO neurons is a powerful tool for dissociating FMRPs function via direct protein-protein interactions from its canonical role in translational regulation (Zhan et al, 2020 ; Park et al, 2021 ). Finally, the development of novel FXS models—such as the FMR1 KO rat (Till et al, 2015 ; Golden et al, 2019 ; Auerbach et al, 2021 ) and FXS human derived iPS cells (Telias et al, 2013 ; Bhattacharyya and Zhao, 2016 ) and organoids (Kang et al, 2021 ), will help identify which phenotypes are most highly conserved across species and highlight new treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important for future studies to examine both somatic and dendritic excitability in FMR1 KO animals in combination with plasticity levels. A recent study has added another element to these contrary findings by demonstrating that FMRP can also directly interact with Kv4 channels to change their gating properties, resulting in reduced cellular excitability and increased LTP thresholds in cerebellar granule cells (Zhan et al, 2020 ). Importantly, reintroduction of an FMRP fragment that can bind Kv4 into FMR1 KO mice restored deficits in mossy fiber LTP induction and behavioral hyperactivity assessed via open field test (Zhan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically these studies either involve pharmacological agents, which is poorly localized, or they require a considerable time between the genetic manipulation and the functional/behavioral assay, which means that the homeostatic regulatory systems have likely produced significant changes in function during the lag [45,46]. Despite this, many intriguing roles for potassium channels and their interactions with other regulatory proteins have been identified that are likely critical for normal neuronal function and may underlie neurological and psychiatric disorders [47][48][49][50][51][52]. Our results show that Opto-Kv channels are an important new tool in probing the behavioral roles of ion channels in specific neuronal populations.…”
Section: Plos Onementioning
confidence: 99%
“…Cterminus domain mutations such as R534H and G482S have been predicted to alter RNA binding and recognition (29). In addition, the frame shift mutation (G538fs* 23) in the open reading frame of FMRP has been shown to introduce novel sequences, which drastically alter the cellular localization of FMRP (30). These mutational studies emphasize the probable structural defects and the contribution of individual domains of FMRP.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies address the mechanism of these interactions through truncations and mutations of FMRP. The N-terminus domain of FMRP is shown to modulate the expression and activity of several ion channels (22,23) while the RGG domain in the C-terminus is implicated in RNA binding and consequent gene expression (24,25). Further, the I304N mutation of FMRP, which results in a severe form of FXS, illustrates the importance of KH domains in polysome association and translation regulation (16,26).…”
Section: Introductionmentioning
confidence: 99%